PENGARUH METODE PEMBELAJARAN PROBLEM SOLVING DILENGKAPI DENGAN MEDIA ANDROID TERHADAP HASIL BELAJAR KIMIA SISWA KELAS X IPA SMA MUHAMMADIYAH MASBAGIK - Fena Prayunisa; Muhsinun Muhsinun (JURNAL ILMIAH GLOBAL EDUCATION, 2021)
This study aims to determine the effect of the problem solving learning model equipped with android media on the chemistry learning outcomes of class X science students at SMA Muhammadiyah Masbagik. This research is a quasi-experimental study (pretest-posttest Control Group Design which aims to determine the effect of the application of problem solving learning models equipped with android media on the learning outcomes of students in class X IPA SMA Muhammadiyah Masbagik. The learning model applied in the experimental class is a problem solving learning model equipped with android media, while the learning model applied in the control class is a conventional learning model.The pretest results obtained in the experimental class by applying the Problem Solving learning model assisted by android media obtained an average value of 30.5 while the pretest value in the control class obtained an average value – an average of 35. Meanwhile, the posttest score in the experimental class by applying creative problem solving models obtained an average value of 80.25, while in the control class by applying the direct learning model the average value was obtained. ta is 67.5. This shows that the problem solving learning model assisted by android media is better than the conventional learning model.